2019
DOI: 10.1088/2515-7620/aaecac
|View full text |Cite
|
Sign up to set email alerts
|

Does strong vertical wind shear certainly lead to the weakening of a tropical cyclone?

Abstract: This is a preliminary pilot study giving an important insight into the feasible improvement of existing prediction of tropical cyclone (TC) intensity change by revisiting the relevant impact of vertical wind shear (VWS), where VWS is commonly defined as the environmental horizontal wind difference between the top and bottom of the shear layer. Macroscopically, strong VWS has been concluded to be detrimental to TC intensification. However, this study, from the microscopic point of view, shows that given the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Energy input from the surface may have significant effects on convection near the TC center (Xu and Wang, 2010a;Chan et al, 2019). The surface latent flux was not significantly different near the TC center when comparing large and small TCs (Figure 9), indicating that the surface latent heat flux did not directly influence the changes in intensity and that those changes were more related to the dynamic and thermodynamic processes associated with VWS.…”
Section: Frontiers In Earth Sciencementioning
confidence: 97%
“…Energy input from the surface may have significant effects on convection near the TC center (Xu and Wang, 2010a;Chan et al, 2019). The surface latent flux was not significantly different near the TC center when comparing large and small TCs (Figure 9), indicating that the surface latent heat flux did not directly influence the changes in intensity and that those changes were more related to the dynamic and thermodynamic processes associated with VWS.…”
Section: Frontiers In Earth Sciencementioning
confidence: 97%
“…11c overlaps with the boundary layer, which accelerates the inflow speed of the main secondary circulation. A stronger boundary layer inflow favors the angular momentum accumulation in the rainbands, which makes the TC outer circulation grow (Chan and Chan 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the lower inertial stability in the outer weaker wind regions (compared to the core) provides less resistance to the radially inward motion in response to the heating gradient. In other words, the radial heating gradient change can be relatively small at large radii (compared to near the core), but there will be a response of radial momentum inflow in this low-inertial-stability region (Chan et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Gray [1] listed six basic conditions favoring TC genesis, namely: (i) sea surface temperature (SST) exceeding 26 • C, (ii) enhanced mid-troposphere (700 hPa) relative humidity, (iii) conditional instability, (iv) enhanced lower troposphere relative vorticity, (v) weak vertical environmental wind shear (VWS) and (vi) a displacement by at least 5 • latitude away from the equator. Chan et al [2] suggested that VWS is one of the main governing factors of both tropical cyclogenesis and tropical cyclone intensity. Moreover, some studies indicate that the uncertainties in forecasting the environmental wind shear values prevent the improvements in TC intensity forecast [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Although some literature has shown cases of cyclones intensifying under moderate to strong VWS (e.g., [8][9][10]), in general large values of VWS are considered to be detrimental to the formation as well as the intensification of TCs, due to the "ventilation" effect [1,[11][12][13]. Chan et al [2] have indicated that the reduction of ventilation above the boundary layer due to vertical alignment is crucial to accumulate the energy within the inner core region of a TC. Nolan and McGauley [6] studied the relationship between VWS and TC genesis events within the latitudes 20 • S and 20 • N from 1969 to 2008, and found that VWS values in the range of 1.25-5 m/s are the most favorable for TC genesis, although previous studies suggested VWS values between 5-10 m/s (e.g., [14]).…”
Section: Introductionmentioning
confidence: 99%